Periodontal Disease and its Association with Angiographically Verified Coronary Artery Disease - Domagoj Vražić; Zoran Miovski; Maja Strozzi; Ivan Puhar; Ana Badovinac; Darko Božić; Darije Plančak (University of Zagreb. School of Dental Medicine, 2015)
Purpose: The aim of this research was to investigate the association of chronic and aggressive periodontitis with the severity of coronary artery disease which was angiographically verified. Material and methods: Subjects were selected among the hospitalized patients at the University Hospital Centre Zagreb who had coronary angiography done because of the chest pain. Thorough clinical examination included periodontal indices and clinical and socio-demographic characteristics of participants. Subjects were divided in two test groups, acute coronary syndrome (ACS) and stable coronary artery disease (CAD), and the control group with no significant CAD. Data were analyzed using Kruskal-Wallis and Pearson's Chi-Square test. Results: From 106 subjects, 66 (62.3%) were hospitalized for ACS, 22 (20.7%) had stable CAD and only 18 (17.0%) had no significant CAD. Only 26 (24.5%) out of 106 patients were never smokers (p<0.05). Chronic periodontitis was the most common finding with 68.2% in ACS group and 54.5% in stable CAD group, while healthy patients without periodontitis (72.6%) were dominant in the control group (p<0.001). Stable CAD group had the highest mean probing depth (PD) 3.92±1.16, gingival recession (GR) 1.34±0.78, clinical attachment level (CAL) 4.60±1.41 and bleeding on probing (BOP) 45.98±26.19 values, whereas ACS group had mean PD value of 3.77±0.91, GR 1.11±0.66, CAL 4.32±1.08 and BOP 41.30±22.09, and no significant CAD group had mean PD value of 3.27±0.97, GR 0.69±0.37, CAL 3.62±1.04 and BOP 26.39±13.92 (p<0.05). Conclusion: Periodontitis was shown to be associated with angiographically verified coronary artery disease. Physical inactivity, poor oral hygiene and periodontal inflammation were observed in patients with ACS and stable CAD.